Study Of the Status of Potassium Nutrients and Soil Ph on Rice Lands in Kolongan Village, Kalawat District - Aibekob, Victor George; Rondonuwu, Jenny Jeanette; Kawulusan, Rafli Irland (Soil and Environment Journal, 2024)
This study aims to determine the status of potassium nutrients and soil pH in Kolongan Village, Kalawat District, and the North Minahasa Regency. This research was conducted from October to November 2022. The research method used was a survey method to determine individual sample points, and then soil samples were tested using the Paddy Soil Test Device (PUTS). Soil samples were then analyzed using the Descriptive analysis method. The results showed that the potassium level at the research site was high while the pH level at the site was slightly acidic and neutral. Keywords: Kalium, pH, Paddy fields area Abstrak Penelitian ini bertujuan untuk mengetahui status hara kalium dan pH tanah di Desa Kolongan, Kecamatan Kalawat, Kabupaten Minahasa Utara. Penelitian ini dilaksanakan pada bulan Oktober sampai dengan November 2022. Metode penelitian yang digunakan adalah metode survei untuk menentukan titik sampel individual, kemudian sampel tanah diuji menggunakan Alat Uji Tanah Padi (PUTS). Sampel tanah kemudian dianalisis menggunakan metode analisis Deskriptif. Hasil penelitian menunjukkan bahwa kadar kalium di lokasi penelitian tergolong tinggi sedangkan kadar pH di lokasi penelitian tergolong agak masam dan netral. Kata kunci: Kalium, pH, Paddy fields area